Analisis Pendapatan Pedagang Daging Ayam Broiler di Pasar Tanjung Pura - Shifwah Ufairah Kusuma; Kurniawan Sinaga (Lembaga Pengembangan Kinerja Dosen, 2025)
As a key source of animal protein in Indonesia with growing demand, this study examines the income levels of broiler chicken meat vendors at Tanjung Pura Market, Langkat Regency. Despite fluctuating prices and limited purchasing power among consumers, traditional markets continue to serve an essential function in meat distribution. The objective of this research is to assess the income of broiler chicken sellers by analyzing production costs, output, profits or losses, R/C ratio, and break-even point (BEP). Using a total sampling method, ten vendors at Tanjung Pura Market were chosen as the research subjects. A qualitative approach was applied through descriptive analysis.